2018
DOI: 10.3390/molecules23113017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hazardous Elements in Children Toys: Multi-Elemental Determination by Chromatography and Spectrometry Methods

Abstract: This paper presents the results of determination of hazardous metal (Cd, Cu, Cr, Hg, Mn, Ni, Pb, Zn) and metalloid (As, Sb) levels in toys available in the Polish market. Two independent sample preparation methods were used to determine the concentration and content of the metals and metalloids. The first one is defined by the guidelines of the EN-71 standard and undertook extraction in 0.07 mol/L HCl. This method was used to conduct speciation analysis of Cr(III) and Cr(VI), as well as for the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Ni only exceeded in 1 sample in the highest quantity that is Study boy (DCT08) 3000.1mg/kg however in that sample Pb and Cd were not detected although other elements Zn, Cr, Mn, and Cu were detected in lesser quantities. Series of experiments in past literature indicated low levels of contaminations also detected in toys that are (Leal, Catarino et al 2016, Sobhanardakani and Babaei 2016, Karaś and Frankowski 2018, Al Kindi and Ali 2020, Mohammed, Dial et al 2020) on the other hand in most literature levels of Zn, Cr, Ni, Cu, Mn were reported in high quantities (Al-Qutob, Asafra et al 2014, Ismail, Mohamad et al 2017.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ni only exceeded in 1 sample in the highest quantity that is Study boy (DCT08) 3000.1mg/kg however in that sample Pb and Cd were not detected although other elements Zn, Cr, Mn, and Cu were detected in lesser quantities. Series of experiments in past literature indicated low levels of contaminations also detected in toys that are (Leal, Catarino et al 2016, Sobhanardakani and Babaei 2016, Karaś and Frankowski 2018, Al Kindi and Ali 2020, Mohammed, Dial et al 2020) on the other hand in most literature levels of Zn, Cr, Ni, Cu, Mn were reported in high quantities (Al-Qutob, Asafra et al 2014, Ismail, Mohamad et al 2017.…”
Section: Resultsmentioning
confidence: 96%
“…Human oral exposure to Cr(VI) has causes hepatotoxicity, which may lead to primary liver cancer and increase the likelihood of cancer patients' deterioration. Zagury 2014, Karaś andFrankowski 2018). Zinc(Zn), Nickel(Ni), Copper(Cu), and Manganese(Mn) are essential for life and are important requirements for good health, but excess and long-term exposure can be harmful and cause health di culties.…”
Section: Introductionmentioning
confidence: 99%
“…Under this framework, we decided first to develop an analytical method based on liquid chromatography inductively coupled plasma mass spectrometry (LC-ICP-MS), to gain improved sensitivities with respect to traditional colorimetric methods [20,21,33] and to allow for the monitoring of the Cr(III)/Cr(VI) interconversion processes by speciated isotope dilution [31,34]. In parallel, it was necessary to develop a novel separation strategy, since the commonly employed Cr(III)/Cr(VI) LC separation methods cannot bear the presence of huge amounts of Cr(III) [33,35]. This developed method was subsequently used to confirm the suspected failure of the official methods in trying to yield reliable Cr(VI) concentrations in the particulate matter sampled in different leather industries.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, huge amounts of gaseous, liquid and solid waste containing chromium compounds are discharged into air, surface water, and soil, causing their contamination. Moreover, products manufactured with the use of chromium-containing pigments, may also be contaminated with this metal, e.g., textiles and toys [1,4]. Chromium present in contaminated soil can be taken up by plants and passed through the trophic chain to humans, or it can permeate into ground water.…”
Section: Introductionmentioning
confidence: 99%